Impacts of Climate Change on the Plant Water Interactions - Turyasingura, Benson; Ayiga, Natal (Journal of Resources Development and Management, 2023)
Climate change has an impact on ecosystem structure and function globally by altering the relationships between plants and soil organisms. Despite the fact that water is the most plentiful molecule on Earth's surface, water scarcity is the element that most severely limits global terrestrial plant production. Little is known about the climatic factors that drive phenological responses to climate change, and less attention has been paid to the fact that phenology is also responsive to other climatic. The aim of this study was to assess the impacts of climate change on plant water interactions. This study was guided by the specific objectives, which included examining the relationship between climate change and plant function; finding out the impacts of climate change on plant water interactions; and assessing how plants handle water scarcity. It was found that there was a linkage between climate change and plant function. The evaporation of water molecules from the outer surfaces of the mesophyll cells initiates the upward transpiration pull in the leaves, and respiring starches and sugars are created during photosynthetic processes using sunlight energy. Climate change enhanced the most enormous movement of species that has occurred without direct human intervention. It was also found that precipitation was a key driver of phenological changes in desert ecosystems. It was also found that drought was one of the most significant biotic challenges faced by plants, with considerable genetic variation in water deficit responses. There is a need for research on climate change to ease biodiversity conservation.